FRI0475 Lung damage in patients with microscopic polyangiitis. (12th June 2018) - Shchegoleva, E.; Zykova, A.; Bulanov, N.; Meshkov, A.; Novikov, P.; Moiseev, S.
Abstract : Objectives: We evaluated the frequency of clinical and CT features of lung damage in patients with microscopic polyangiitis (MPA). Methods: We enrolled 97 patients with MPA, that was diagnosed according to CHCC2012. The median age at disease onset was 50.7±16.6 (M±SEM) years, the median duration of follow-up was 47.6±47.5 (M±SEM) months. 64 (66.0%) patients were ANCA-MPO-positive, 24 patients (24.7%) were ANCA-PR-3-positive, and 9 (9.3%) patients had undifferentiated ANCA. Diffuse alveolar haemorrhage (DAH) was diagnosed by the presence of dyspnea, hemoptysis, anaemia and pulmonary infiltrates on chest CT. Results: Lung damage was diagnosed in 77 (79.4%) patients. 43 (55.8%) patients had pulmonary damage at the disease onset, while 34 (44.2%) patients developed signs of lung involvement within 8.0±4.1 (M±SEM) months. At baseline, the median pulmonary BVAS was 4. 2; 6 The interstitial changes occurred in more than half of cases at the onset of the disease. The most frequent CT-patterns included pulmonary infiltrates (n=49) and ground-glass opacity (n=39) (table 1). DAH developed in 30 (30.9%) patients, among them 15 (15.5%) had DAH at the onset of the disease. The pulmonary fibrosis was the most common CT-pattern at the end of follow-up (52 patients). Notably, interstitial damages at the onset of disease were associated with the development of fibrotic changes (OR=4.7, 95% CI 1.7–12.9) and bronchiectasis (OR=9.8, 95% CI 1.2–78.3) at the end of follow-up. The median of pulmonary VDI was 1 (0;4) at the end of the follow up. PR-3-positive group had higher occurrence of consolidations at the end of the follow-up as compared to patients with anti-MPO-antibodies (53.8% versus 16.0%, p=0.023). The pulmonary fibrosis was the most common CT-pattern at the end of follow-up (52 patients). Notably, interstitial damages at the onset of disease were associated with the development of fibrotic changes (OR=4.7, 95% CI 1.7–12.9) and bronchiectasis (OR=9.8, 95% CI 1.2–78.3) at the end of follow-up. The median of pulmonary VDI was 1 (0;4) at the end of the follow up. PR-3-positive group had higher occurrence of consolidations at the end of the follow-up as compared to patients with anti-MPO-antibodies (53.8% versus 16.0%, p=0.023). Conclusions: In patients with MPA, the CT signs of interstitial damage were usually reversible. However, they predicted a higher incidence of lung fibrosis and bronchiectasis at the end of follow-up. DAH occured in one third of patients with MPA. Disclosure of Interest: None declared